Importance of real-time RT-PCR to supplement the laboratory diagnosis in the measles elimination program in China. - Aili Cui (PLoS ONE, 2018)
In addition to high vaccination coverage, timely and accurate laboratory confirmation of measles cases is critical to interrupt measles transmission. To evaluate the role of real-time reverse transcription-polymerase chain reaction (RT-PCR) in the diagnosis of measles cases, 46,363 suspected measles cases with rash and 395 suspected measles cases without rash were analyzed in this study; the cases were obtained from the Chinese measles surveillance system (MSS) during 2014-2017 and simultaneously detected by measles-specific IgM enzyme-linked immunosorbent assay (ELISA) and real-time RT-PCR. However, some IgM-negative measles cases were identified by real-time RT-PCR. The proportion of these IgM-negative and viral nucleic acid-positive measles cases was high among measles cases with measles vaccination history, cases without rash symptoms, and cases within 3 days of specimen collection after onset. The proportion of IgM-negative and viral nucleic acid-positive measles cases in the 0-3 day group was up to 14.4% for measles cases with rash and 40% for measles cases without rash. Moreover, the proportions of IgM-negative and nucleic acid-positive measles cases gradually increased with the increase in the measles vaccination dose. Therefore, integrated with IgM ELISA, real-time RT-PCR would greatly improve the accurate diagnosis of measles cases and avoid missing the measles cases, especially for measles cases during the first few days after onset when the patients were highly contagious and for measles cases with secondary vaccine failure. In conclusion, our study reconfirmed that IgM ELISA is the gold-standard detection assay for measles cases confirmation. However, real-time RT-PCR should be introduced and used to supplement the laboratory diagnosis, especially in the setting of pre-elimination and/or elimination wherever appropriate.